Effects of Pollution on Marine Organisms. (1st October 2017) - Mearns, Alan J.; Reish, Donald J.; Oshida, Philip S.; Morrison, Ann Michelle; Rempel‐Hester, Mary Ann; Arthur, Courtney; Rutherford, Nicolle; Pryor, Rachel
Abstract : This review covers selected 2016 articles on the biological effects of pollutants and human physical disturbances on marine and estuarine plants, animals, ecosystems and habitats. The review, based largely on journal articles, covers field and laboratory measurement activities (bioaccumulation of contaminants, field assessment surveys, toxicity testing and biomarkers) as well as pollution issues of current interest including endocrine disrupters, emerging contaminants, wastewater discharges, dredging and disposal etc. Special emphasis is placed on effects of oil spills and marine debris due largely to the 2010 Deepwater Horizon oil blowout in the Gulf of Mexico. Several topical areas reviewed in the past (ballast water and ocean acidification) were dropped this year. The focus of this review is on effects, not pollutant fate and transport. There is considerable overlap across subject areas (e.g.some bioaccumulation papers may be cited in other topical categories). Please use keyword searching of the text to locate related but distributed papers. Use this review only as a guide and please consult the original papers before citing them.